Fototerapi dalam Dermatologi - Inda Astri Aryani; Maria Mayfinna Gozali; Indri Widyasari (Conferences of Medical Sciences Dies Natalis, 2019)
Phototherapy is a therapeutic procedure in dermatology. Phototherapy uses certain ultraviolet wavelengths classified into 3 types,broadband UVB (BBUVB), narrowband UVB (NBUVB), and psoralen UVA (PUVA). The most widely used is NBUVB for treating psoriasis, atopic dermatitis and vitiligo. The mechanism of action of phototherapy is to reduce epidermal proliferation, suppress the immune system, reduce the inflammatory process, and induce repigmentation. Before starting phototherapy, the dose adjustment depends on skin type and minimal erythema dose (MED). Frequency of use is recommended based on the severity of the disease, continuously administered needed. Besides of this therapeutic effect, some contraindications and side effects that need to be considered in the use of phototherapy such as drug interactions, photoallergic and risk of skin malignancy.